Open-Label Adhesion Performance Studies of a New Lidocaine Topical System 1.8% versus Lidocaine Patches 5% and Lidocaine Medicated Plaster 5% in Healthy Subjects - Gudin, Jeffrey; Webster, Lynn R; Greuber, Emileigh; Vought, Kip; Patel, Kalpana; Kuritzky, Louis (Journal of pain research, 2021)
The primary objective was to evaluate adhesion performance of the lidocaine topical system 1.8% for 12 hours in healthy human subjects in three studies: as a single product (Study 1) and versus other lidocaine topical products (lidocaine patch 5% and lidocaine medicated plaster 5% [Study 2] and generic lidocaine patch 5% [Study 3]). Safety of the lidocaine topical system 1.8%, with a skin irritation focus, was a secondary objective. All three studies were open-label, randomized, Phase 1 adhesion performance studies in healthy adult volunteers (N=125). Lidocaine topical products were applied for 12 hours per test, per study arm. Adhesion of all test products was scored at 0, 3, 6, 9, and 12 hours post-application. Skin irritation was scored after product removal or when a product detached. Overall, the majority (≥75%) of subjects treated with the lidocaine topical system 1.8% demonstrated ≥90% adhesion (FDA adhesion score 0) throughout the 12-hour administration period versus 13.6% of subjects treated with lidocaine patch 5%, 15.9% of subjects treated with lidocaine medicated plaster 5%, and 0% of subjects treated with the generic lidocaine patch 5%. There were no complete detachments with the lidocaine topical system 1.8%, whereas 4.5% of lidocaine patch 5% and lidocaine medicated plaster 5% detached, and 29% of generic lidocaine patch 5% detached. Minimal skin irritation was observed with each lidocaine topical product. Across three studies, lidocaine topical system 1.8% demonstrated superior adhesion performance versus the three other products tested. Skin irritation was minimal across products and studies. NCT04312750, NCT04320173, NCT04319926.